Coping with crises in entrepreneurship and effectuation - Lima, Edmilson de Oliveira; Moreira Silva, João Paulo; Lopes, Rose Mary Almeida; Cunha, Julio Araújo Carneiro da (REGEPE Entrepreneurship and Small Business Journal, 2024)
Objective: This theoretical essay examines the processes by which crises are experienced and managed by entrepreneurs, with a particular focus on the role of effectuation. Problem: The nature, intensity, and duration of crises vary, exerting pressure on organizations and entrepreneurs. In order to respond effectively, it is necessary to develop quick, ingenious solutions that are adapted to the context of uncertainty and lack of resources. However, there is a lack of clarity regarding the occurrence of crises for entrepreneurs and the strategies they employ to cope with them. Originality: The study, based on a characterization of crises and their diversity, delves more profoundly into the ways in which entrepreneurs cope with crises and the extent to which effectuation is (or fails to be) useful in such coping. It illuminates the micro and macro levels of crises and the nuances in responses to them. Social/management contributions: In addition to presenting new research conclusions, the essay proposes a research agenda for prospective publications that seek to address humanity's significant challenges.